2016
DOI: 10.1074/jbc.m115.662403
|View full text |Cite
|
Sign up to set email alerts
|

The Polycomb Repressive Complex 1 Protein BMI1 Is Required for Constitutive Heterochromatin Formation and Silencing in Mammalian Somatic Cells

Abstract: Background: BMI1 silences the expression of genes located at the facultative heterochromatin. Results: BMI1 is abundant at repetitive genomic regions, including the pericentromeric heterochromatin (PCH), where it is required for compaction and silencing. Conclusion: BMI1 is essential for PCH formation. Significance: BMI1 function at PCH is important to understand how BMI1 regulates genomic stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 79 publications
3
34
0
Order By: Relevance
“…This is consistent with previously published findings that H2AK119 monoubiquitination by PRC1 is associated with gene repression (Cao et al, 2005; Wang et al, 2004). It is also possible that knockdown of Bmi1 de-compacted chromatin and increased DNA accessibility (Abdouh et al, 2016; Eskeland et al, 2010; Francis et al, 2004; Levine et al, 2002; Shao et al, 1999), thereby de-repressing Gata4 and the other cardiogenic genes. Interestingly, this de-repression of endogenous Gata4 by Bmi1 depletion could substitute for exogenous Gata4 in reprogramming fibroblasts into beating iCMs, demonstrating that removing certain epigenetic barrier(s) could allow for efficient iCM generation with fewer transcription factors.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with previously published findings that H2AK119 monoubiquitination by PRC1 is associated with gene repression (Cao et al, 2005; Wang et al, 2004). It is also possible that knockdown of Bmi1 de-compacted chromatin and increased DNA accessibility (Abdouh et al, 2016; Eskeland et al, 2010; Francis et al, 2004; Levine et al, 2002; Shao et al, 1999), thereby de-repressing Gata4 and the other cardiogenic genes. Interestingly, this de-repression of endogenous Gata4 by Bmi1 depletion could substitute for exogenous Gata4 in reprogramming fibroblasts into beating iCMs, demonstrating that removing certain epigenetic barrier(s) could allow for efficient iCM generation with fewer transcription factors.…”
Section: Discussionmentioning
confidence: 99%
“…The polycomb-group (PcG) proteins traditionally represent another type of chromatin repression normally enriched on facultative heterochromatin together with H3K27me3 and H2AK119ub, and are traditionally not considered associating with pericentromeric heterochromatin (18,19). However, several studies have demonstrated that under some circumstances, PcG proteins can be found on pericentromeric satellite DNA (20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…Although PcG proteins are generally considered regulators of facultative chromatin, thus regulating gene expression, PcG proteins have also been demonstrated to be involved in the formation of constitutive heterochromatin [16,[42][43][44][45]. Constitutive heterochromatin is found mainly at the centromeric and telomeric regions of chromosomes, which are gene-poor regions crucial for maintaining structural organization of chromosomes and genomic integrity.…”
Section: The Role Of Pcg Complexes In Repression Of Pericentromeric Hmentioning
confidence: 99%
“…PCH is kept in an inactive state by the continuous repression facilitated by the SUV39H/H3K9me3/HP1/DNMT pathway. However, in specific developmental settings [16,[42][43][44] or in malignancies [45,[50][51][52], hypomethylation of PCH allows the deposition of PcG. In early mouse preimplantation embryos, maternal PCH is enriched in H3K9me3, HP1 and H4K20me3 mediated by SUV39H1/2 and SUV420H1/2.…”
Section: The Role Of Pcg Complexes In Repression Of Pericentromeric Hmentioning
confidence: 99%
See 1 more Smart Citation